If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 42 + x = 56 Solving 42 + x = 56 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + x = 56 + -42 Combine like terms: 42 + -42 = 0 0 + x = 56 + -42 x = 56 + -42 Combine like terms: 56 + -42 = 14 x = 14 Simplifying x = 14
| y=1/4*x^2-x-7 | | 8.7b-0.4=17 | | 7-3x+8+2x-2=8+2*5 | | N-24=31 | | 4x+64+45=7/2 | | 27-p=3 | | 8/10=a/6 | | (a/b)=10a | | 2.2r+0.47=1.79 | | T+22=57 | | 43=6.2x+2.4x | | j/9-9=5/6 | | 0.13y-0.6=0.83 | | M-21=34 | | 5y-19=2(y-5) | | Y-19=18 | | 13y-0.6=0.83 | | 348=47h-18h | | 5/1 | | 18+p=22 | | 08d+0.4=0.96 | | 3*x+5-2= | | 3.4m+4.6m=72 | | 39-r=34 | | -3a+10a=49 | | 18+q=25 | | R-15=24 | | 8c+9c=51 | | X^3+2x-5=0 | | 1/3x+5=8 | | 36+s=45 | | 28y-14y=-42 |